Spatial-temporal variation in litterfall in seasonally dry tropical forests in Northeastern Brazil - Araújo,V. F. P. (2020)
Abstract The production of litterfall is essential for nutrient cycling in terrestrial ecosystems. From November 2009 to October 2011, analyzed the monthly litterfall production in two areas of Caatinga, a type of Seasonally Dry Tropical Forest located in the Cariri Paraibano, in the semiarid region of the Paraíba, Northeastern Brazil. One of the areas, Private Natural Heritage Reserve (RPPN) Fazenda Almas, is legally protected, and the other, Fazenda Moreiras, does not. The aims were to evaluate the effects of precipitation, evapotranspiration and vegetation structure on the temporal and spatial dynamics of litterfall production. Eight sampling points were randomly chosen at each site, and two 1 m2 collectors were installed 50 m apart from each other. The collected material was sorted, dried and weighed. Additionally, the characteristics (density, species richness, height and mean basal area) of the tree-shrub stratum in plots with a 10 m radius surrounding each collector. Total litterfall production was 4,500 kg ha-1 yr-1 for Fazenda Almas and 3,300 kg ha-1 yr-1 for Fazenda Moreiras; these values were within the expected range for Seasonally Dry Tropical Forests. The inter- and intra-annual variation in litterfall production was positively correlated with precipitation and evapotranspiration rates, and four months after the highest precipitation rates, there was a marked decrease in litterfall occurred during the dry season. Furthermore, the contributions of the material fractions were distinct with the leaf fraction representing for more than 60% of the litterfall, and the vegetation structure explained 75% of the variation in litterfall production. Therefore, climatic factors and vegetation structure affect the temporal and spatial dynamics of litterfall production and consequently influence nutrient dynamics in the semiarid region of Brazil.